2001
DOI: 10.1081/cnv-100103852
|View full text |Cite
|
Sign up to set email alerts
|

The HER-2/neuOncogene in Tumors of the Gastrointestinal Tract

Abstract: The HER-2/neu oncogene is localized to chromosome 17q and shares significant homology with the epidermal growth factor receptor. As a result of its potential role in the selection of therapy, HER-2/neu testing has reached near-standard-of-practice status in breast cancer. There is considerable interest in HER-2/neu as a prognostic factor and target of therapy in tumors of the gastrointestinal tract. In this review of HER-2/neu expression in esophageal squamous cell carcinoma and adenocarcinomas of the esophagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
158
1
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(168 citation statements)
references
References 57 publications
2
158
1
7
Order By: Relevance
“…For all of these tumor entities, HER-2 positivity (overexpression and/or amplification) had been previously described. [29][30][31][32] For example, HER-2 positivity for gastric cancer has been Of most tumor categories, we analyzed around 50 cases or even fewer. This rather low number raises the possibility that rare HER-2 amplification/overexpression may have been missed in some tumor entities.…”
Section: Discussionmentioning
confidence: 99%
“…For all of these tumor entities, HER-2 positivity (overexpression and/or amplification) had been previously described. [29][30][31][32] For example, HER-2 positivity for gastric cancer has been Of most tumor categories, we analyzed around 50 cases or even fewer. This rather low number raises the possibility that rare HER-2 amplification/overexpression may have been missed in some tumor entities.…”
Section: Discussionmentioning
confidence: 99%
“…3,22,28 ERBB2 staining in gastric cancer is not directly correlated to ERBB2 amplification, with up to 30% of ERBB2 amplification-positive cases showing only focal staining or diffuse staining in o 30% of tumor cells. 24 On the contrary, ERBB2 protein expression and gene amplification in our colorectal cancer samples tallied quite accurately. None of the ERBB2 expression-negative colorectal cancer was amplified, whereas all immunohistochemistry-positive colorectal cancers were, leaving only the equivocal staining tumors in a grey zone.…”
Section: Discussionmentioning
confidence: 99%
“…It focused on ERBB2 amplification, as preclinical data supporting the HERACLES trial suggested amplification and not only overexpression as the predictive marker for response to anti-ERBB2 treatment. 10 Within this algorithm, to minimize false positives owing to unspecific staining, we disregarded cytoplasmic ERBB2 expression, 19,24 as in breast cancer only membrane-bound ERBB2 expression is associated with ERBB2 gene amplification. 19 As in breast cancer, in our colorectal cancer series, ERBB2 overexpression associated with gene amplification was also already clearly membrane bound at low magnification.…”
Section: Discussionmentioning
confidence: 99%
“…26 Gastric cancers of intestinal type have also shown higher rates of expression of HER2 protein than gastric cancer of diffused type (p<0,05) in one Korean study. 27 In the published studies it is determined that proximal gastric cancers with intestinal phenotype have higher existence of HER2 expression than distal diffused gastric cancers ( Before it came to the knowledge of existence of prognostic factors on molecular level, clinicalpathological parameters were the only one known predictive and prognostic factors until then. To the recent proven prognostic variables belong the tumor stage, histological gradus, tumor size, localization, existence of lymphovascular invasion, age and gender of the patient, and molecular tumor markers p53, E-cadherin, CD-34, cErbB2, CA 72-4, CEA which recently gained popularity as potential prognostic indicators for predicting the tumor behavior.…”
Section: Discussionmentioning
confidence: 99%